IMPLEMENTASI KEBIJAKAN PENGELOLAAN PASAR BUAH RAWA BANGUN DI KABUPATEN SANGGAU - Berlinus Endo E.42009014 (FISIP Universitas Tanjungpura Pontianak, 2022)
Thesiswritingis intendedtoidentify anddescribe the process ofimplementation ofmanagement policiesSwampfruitmarketBangundithe District. The title ofthis thesiswas appointedbased onthe existing problemsin theimplementationprocess ofstructuringandregionalmarketstreet vendors (PKL), Implementation oftheprogramrefers toSanggaudecreeNo. 33of 2009 onRegional GovernmentMarketsStructuringandDeterminationZoneStreet Vendors.District Government, particularly the Dinas Perindustrian, Perdagangan, Koperasi dan UKMSector is Leading in the implementation process of market management, the results of the study indicate that the process of implementation and the establishment of regional market management vendors (PKL) is not going well due to the lack of communication of the implementor of the street vendors and Resources.Lack ofcommunicationandthesupportofthe GovernmentResourcesDistrictto makethe process ofimplementation ofthe program would beless than optimal. Whilethe traderswhodo thebuying and sellingof merchandisewas not satisfiedandlesstouchingpiecesof streetvendors. Keywords: Public Policy, Public PolicyImplementation, Market Management.